2016
DOI: 10.18805/ajdfr.v0iof.9615
|View full text |Cite
|
Sign up to set email alerts
|

Effect of incorporation of Paneer whey on dough characteristics and organoleptic attributes of milk bread

Abstract: Study was conducted to assess the effect of substitution of water with paneer whey in bread making on the dough characteristics and organoleptic attributes of milk bread. Water was substituted with paneer whey in four different percentages .i.e. 25%, 50%, 75% and 100%. The dough development time and dough stiffness were increased with increase in the level of incorporation of paneer whey. The means of sensory scores of milk breads ranged between 84.18 ± 2.09 and 86.83 ± 2.57. Sensory scores of milk bread sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…An increase of the sensory characteristics of baladi bread was reported by Gaber et al [ 92 ], due to the content of organic acids, lactose and salts of the acid whey. Improved sensory characteristics were also obtained by Kakan et al [ 93 ] for milk bread and by Paul et al [ 4 ] for multigrain bread, with water replacement by Paneer whey. Our results, showing no statistically significant differences compared to the control, can probably be due to the lower amounts of dairy ingredients compared to those used in other studies.…”
Section: Discussionmentioning
confidence: 84%
“…An increase of the sensory characteristics of baladi bread was reported by Gaber et al [ 92 ], due to the content of organic acids, lactose and salts of the acid whey. Improved sensory characteristics were also obtained by Kakan et al [ 93 ] for milk bread and by Paul et al [ 4 ] for multigrain bread, with water replacement by Paneer whey. Our results, showing no statistically significant differences compared to the control, can probably be due to the lower amounts of dairy ingredients compared to those used in other studies.…”
Section: Discussionmentioning
confidence: 84%
“…Industrial utilization of fluid whey is limited mainly due to the low dry matter content and the variability of chemical composition. Fluid whey may substitute water or milk in bread and other bakery and confectionery products, in which it enhance crumb structure, crust browning and flavor (Kosikowski 1979;Kakan et al 2015). Marriott et al (1998) reported that fluid whey can replace 30% of water in cured ham formulation.…”
Section: The Use Of Whey and Whey Formulations In The Food Industrymentioning
confidence: 99%